Potensi Tepung Wortel (Daucus carrota L.) dalam Meningkatkan Sifat Antioksidan dan Fisikokimia Sweet Cream Butter. (Faculty of Animal Science Universitas Brawijaya, 2018)
This study aims to determine the effect of addition powder carrot as antioxidant agent to antioxidant activity, fat content, mositure, cholesterol, pH value and melting point of sweet cream butter. The method used was experiment laboratory. The materials used were sweet cream butter and carrot powder and the treatments were the addition of carrot powder 0% (A), 2% (B), 4% (C), and 6% (D) then analyzed about antioxidant activity, fat content, mositure, cholesterol, pH value and melting point of sweet cream butter. The data were analyzed by ANOVA using the basic design of Block Randomized Design (BRD) and continued by Duncan's Multiple Range Test (DMRT) if there was a significantly different. Finding suggested an effect of the addition carrot powder could improve the quality (up to 42.55%) of sweet cream butter which is 6% of carrot powder give the best treatment.